Windows netbooks : the path to low-cost computing - Kelly, James F. (James Floyd) (Berkeley, CA : Apress ; New York, NY : [distributed by] Springer-Verlag, 2009)
Information on buying and using a Windows netbook.
The netbook -- Netbook hardware options -- Netbook maintenance -- Netbook software options -- Netbook and Google Docs -- Netbook malware protection -- Netbook web browsers -- Netbook email -- Netbook calendar -- Netbooks and OpenOffice.org -- Windows 7 and netbooks -- Finding great netbook apps -- Netbook manufacturers -- Upgrading a netbook to Windows 7 -- Additional netbook apps to consider.
Includes index.
Keywords: Netbook computers -- Handbooks, manuals, etc; Laptop computers -- Handbooks, manuals, etc